A dual-functional fluorescent biosensor based on enzyme-involved catalytic hairpin assembly for the detection of APE1 and miRNA-21 - Lu, Xiaoyong; Li, Dan; Luo, Zewei; Duan, Yixiang (Analyst (London), 2022)
Both apurinic/apyrimidinic endonuclease 1 (APE1) and microRNA-21 (miRNA-21) have been reported to be related to tumors, enabling them to be the biomarkers of several cancers. This has led to the development of various biosensors to detect APE1 or miRNA-21. However, biosensors that focus on single target detection are subject to low accuracy. In this work, a fluorescent biosensor based on enzyme-involved catalytic hairpin assembly (CHA) for the detection of APE1 and miRNA-21 was developed, aimed at improving the accuracy of early-phase diagnosis of cancers. Two hairpin structured DNA probes (H1 and H2) were utilized to concatenate the enzyme-assisted circuit and CHA circuit in the system. The stem of H1 with a blunt end was modified with an AP site, while H2 was modified with 6-FAM at the 5′ terminal and Dabcyl at the 3′ terminal. In the presence of APE1, H1 was cleaved from the AP site to expose the toehold sequence. Then, miRNA-21 bound with the toehold sequence to initiate the CHA reaction between H1 and H2. The assembled product of CHA triggered the 6-FAM of H2 at a distance from Dabcyl, which recovered the fluorescence signal. It is worth noting that only under the co-stimulation of APE1 and miRNA-21 can the fluorescence signal be detected, indicating that the biosensor could work as an AND logic gate. The proposed dual-functional biosensor achieved a limit of detection (LOD) of 0.016 U mL −1 for APE1 and 0.25 nM for miRNA-21 and APE1, respectively, and also exhibits good selectivity and stability for the two biomarkers. Thus, the biosensor has great potential to be applied as a new platform for cancer diagnosis. A dual-functional fluorescent biosensor based on enzyme-involved catalytic hairpin assembly (CHA) was developed for the detection of APE1 and miRNA-21, aiming at improving the accuracy of cancer diagnosis in the early phase.